Unilateral Pyosalpinx in an Adult Female presenting with Features of Acute Abdomen: A Case Report (Nepal Medical College Journal, 2021)
Pyosalpinx is defined as collection of pus in the fallopian tube and is a late manifestation of pelvic inflammatory disease. Pelvic inflammatory disease refers to a spectrum of inflammatory changes of the female genital tract. It comprises of endometritis, salpingitis, cervicitis, pyosalpinx, tubo-ovarian abscess and peritonitis. Pyosalpinx may progress to tubo-ovarian abscess which may rupture leading to peritonitis. In addition, pelvic inflammatory disease commonly affects both side of the tube. Thus, early diagnosis and proper intervention plays a great role in the management of pyosalpinx. We report a case of unilateral left sided pyosalpinx which presented with features of acute abdomen.